Public Information Disclosure Communication Strategy at the Regional Liaison Agency of Banten Province - Laksana, Muhibudin Wijaya; Alia, Siti; Nuraeni, Rina (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2024)
The study investigates the communication strategy of the Regional Liaison Agency (BPD) of Banten Province in implementing Public Information Disclosure (KIP) policies, motivated by its classification as an